Life Analysis of Standard Planetary Roller Screw Mechanism based on Structural Parameter - Fu Yongling; Zheng Shicheng; Gan Fajin (Jixie chuandong)
Taking the standard planetary roller screw mechanism for aircraft electro mechanical actuator as the research object,the analytical solution is obtained by calculating the mechanical properties of the fiber,using ANSYS Workbench software for finite element simulation analysis,and the analytical solution is compared with the simulation results,the maximum deviation value of the two is not more than 5%. On this basis,the influence of lead of screw （lead angle） on screw life is analyzed. The results show that with the increase of lead of screw （lead angle）,the life of screw pair gradually increases. It shows that proper increase lead of screw （lead angle）,can improve the life of screw pair. At the same time,the influence of roller root number on the life of screw pair is analyzed. With the increase of roller root number,total contact points increased,and the life of the screw pair will gradually increase. From the point of increasing the life of the screw pair,the more of roller root number is,the better. This research provides the basis for the optimization design and analysis of the planetary roller screw mechanism with high reliability and long life.